DFT Investigation of the Structure and Alkaline Earth Cation Selectivity of 1,4-Diazo-2,3,8,9-dibenzo-7,10-dioxacyclododecane-5,12-dione - Beshkoofeh, S.; Safarpour, M.A.; Saranjam, L.; Varnosafadarani, M.T.M. (Asian Journal of Chemistry, 2013)
Quantum mechanical study of 1,4-diazo-2,3,8,9-dibenzo-7,10-dioxacyclododecane-5,12-dione and its interaction with the alkaline earth dications Be2+, Mg2+, Ca2+ are presented in this article. This compound is used for the construction of a potentiometric carbon paste modified electrode for calcium ion. All calculation is performed at density functional theory (DFT) level of the theory by using the 6-31G* basis set. Initially the geometry optimizations calculations are accomplished, then frequency and basis set superposition error are performed. The geometric optimization calculations are used to obtain the concerned information of geometric structures of the molecule and the HOMO-LUMO energy gap. The frequency calculations are used to obtain the data of thermo-chemistry such as the complex enthalpy and free Gibbs complex energy formation. Our calculations clearly show that the investigated molecule in fact binds Be2+ most strongly in gas phase. Whereas the best selectivity is observed for this molecule in experimental results is Ca2+. Thus, solvation effects appear strongly influence cation selectivity.